PENINGKATAN PENGETAHUAN DAN PERILAKU SIKAT GIGI MELALUI EDUKASI KESEHATAN DI SDN 168294 KOTA TEBING TINGGI - Harahap, Elsa Puspita Sari; Nurhayati, Nurhayati; Saragih, Siti Riani Fadila; Fadillah, Atika; Telaumbanua, Lenta Mesra; Lubis, Nurwasilah Syarif; Asriani, Asriani (Jurnal Abdimas Akademika, 2025)
This article discusses the enhancement of knowledge and behavior regarding tooth brushing through health education at SDN 168294 Tebing Tinggi. Oral health is a fundamental aspect of children's health, with the prevalence of dental issues in Indonesia reaching 57.6%, especially among children aged 5-9 years. Dental caries and poor oral hygiene are the primary concerns. This study implements interactive health education and proper tooth brushing techniques, including the Bass technique. Findings indicate that an educational approach involving parents and teachers can enhance knowledge, change attitudes, and foster positive behaviors in children regarding oral health. Therefore, sustained interventions are necessary to reduce the prevalence of dental problems and improve students' quality of life.